Strong Inhibitory Effect, Low Cytotoxicity and High Plasma Stability of Steroidal Inhibitors of N-Methyl-D-Aspartate Receptors With C-3 Amide Structural Motif - Adla, Santosh Kumar; Slavikova, Barbora; Chodounska, Hana; Vyklicky, Vojtech; Ladislav, Marek; Hubalkova, Pavla; Krausova, Barbora; Smejkalova, Tereza; Nekardova, Michaela; Smidkova, Marketa; Monincova, Lenka; Soucek, Radko; et al. (Frontiers in Pharmacology, 2018)
Herein, we report the synthesis, structure-activity relationship study, and biological evaluation of neurosteroid inhibitors of N-methyl-D-aspartate receptors (NMDARs) receptors that employ an amide structural motif, relative to pregnanolone glutamate (PAG) – a compound with neuroprotective properties. All compounds were found to be more potent NMDAR inhibitors (IC50 values varying from 1.4 to 21.7 μM) than PAG (IC50 = 51.7 μM). Selected compound 6 was evaluated for its NMDAR subtype selectivity and its ability to inhibit AMPAR/GABAR responses. Compound 6 inhibits the NMDARs (8.3 receptors (8.3 ± 2.1 μM) more strongly than it does at the GABAR and AMPARs (17.0 receptors (17.0 ± 0.2 μM and 276.4 ± 178.7 μM, respectively). In addition, compound 6 (10 μM) decreases the frequency of action potentials recorded in cultured hippocampal neurons. Next, compounds 3, 5–7, 9, and 10 were not associated with mitotoxicity, hepatotoxicity nor ROS induction. Lastly, we were able to show that all compounds have improved rat and human plasma stability over PAG.